10-year outcomes of triple-site versus standard cardiac resynchronization therapy randomized trial (TRUST CRT). (25th November 2020) - Mazurek, M; Jedrzejczyk-Patej, E; Kowalski, O; Sredniawa, B; Sokal, A; Pruszkowska-Skrzep, P; Pluta, S; Kukulski, T; Szulik, M; Stabryla-Deska, J; Kalarus, Z; Lenarczyk, R
Abstract: Background: Triple-Site versus Standard Cardiac Resynchronization Therapy Randomized Trial (TRUST CRT) was initiated in 2009 to verify the hypothesis whether triple-site (single right, double left) cardiac resynchronization therapy (CRT) may be superior to conventional, biventricular resynchronization in patients with advanced heart failure. Objectives: To report 6-month outcomes and 10-year survival in TRUST CRT. Methods: 100 consecutive patients with moderate to severe heart failure, ejection fraction of 35% or less, electrical and mechanical dyssynchrony, were randomly assigned in a 1:1 fashion to triple-site CRT defibrillator (TRIV) or to conventional CRT-D. The primary objective evaluated response-rate, defined as the 6-month's combined end point of alive status, freedom from hospitalization for heart failure or heart transplantation, relative≥10% increase in ejection fraction, ≥10% in peak oxygen consumption, and ≥10% in 6-minute walking distance. The secondary objective was to assess the occurrence of major adverse cardiovascular events (hospitalization for exacerbated heart failure requiring modification of pharmacotherapy, heart transplant or death) at month 6 and during remote observation. Results: At month 6, the response-rate was higher in triple-site than conventional CRT-D group (51.1 vs. 26.5%, P=0.014). There were 2 deaths or heart failure events in the triple-site group (4%) as compared with 8 in the group assigned to conventional CRT-D (16%). A triple-site resynchronization resulted in 12% absolute risk reduction for secondary end point (hazard ratio 0.25; 95 percent confidence interval, 0.05 to 1.17, P=0.056, in comparison with the conventional CRT-D group). After 10 years of observation (median follow up of 7.1 years; range: 1.2–10.4) 57 patients (58.2%) died: 24 (53.3%) in the triple-site group, 31 (60.8%) in the conventional group (P=0.46) and 2 patients with and ICD (failed CRT implantation) [Figure]. Conclusions: In patients with advanced heart failure, triple-site resynchronization combined with an ICD did not result in better survival than conventional resynchronization therapy in a median observation of 7.1 years. Funding Acknowledgement: Type of funding source: None